2019
DOI: 10.1523/eneuro.0197-19.2019
|View full text |Cite
|
Sign up to set email alerts
|

Toric Spines at a Site of Learning

Abstract: We discovered a new type of dendritic spine. It is found on space-specific neurons in the barn owl inferior colliculus, a site of experience-dependent plasticity. Connectomic analysis revealed dendritic protrusions of unusual morphology including topological holes, hence termed "toric" spines (n ϭ 76). More significantly, presynaptic terminals converging onto individual toric spines displayed numerous active zones (up to 49) derived from multiple axons (up to 11) with incoming trajectories distributed widely t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 65 publications
0
13
0
Order By: Relevance
“…The cytosol of these spines contains numerous mitochondria, which is generally excluded from typical dendritic spines in the brain (Parajuli et al, 2020a). Similarly, a recent volume EM study in the inferior colliculus of the barn owl reported doughnut-shaped spines with a hole in the center, without any obvious head and neck like features (Sanculi et al, 2020). Recently, by three-dimensional reconstruction of FIB-SEM images, we revealed atypical U-shaped dendritic protrusions from dendrites of neurons in the interpeduncular nucleus (Parajuli et al, 2020b).…”
Section: Three-dimensional Morphology and The Presynaptic Contacts Of Dendritic Spinesmentioning
confidence: 91%
See 1 more Smart Citation
“…The cytosol of these spines contains numerous mitochondria, which is generally excluded from typical dendritic spines in the brain (Parajuli et al, 2020a). Similarly, a recent volume EM study in the inferior colliculus of the barn owl reported doughnut-shaped spines with a hole in the center, without any obvious head and neck like features (Sanculi et al, 2020). Recently, by three-dimensional reconstruction of FIB-SEM images, we revealed atypical U-shaped dendritic protrusions from dendrites of neurons in the interpeduncular nucleus (Parajuli et al, 2020b).…”
Section: Three-dimensional Morphology and The Presynaptic Contacts Of Dendritic Spinesmentioning
confidence: 91%
“…Perhaps the recently described toric spine represents a prominent example of multiple synaptic inputs that converge onto a single spine. A single toric spine receives synaptic inputs from as many as 11 different axons (Sanculi et al, 2020 ). This connectivity design is different from that of mossy fiber inputs onto CA3 thorny excrescence spines, where multiple synaptic inputs (as many as 37 synaptic contacts) are made onto one spine by a single presynaptic bouton (Chicurel and Harris, 1992 ).…”
Section: Three-dimensional Morphology and The Presynaptic Contacts Of Dendritic Spinesmentioning
confidence: 99%
“…The prevalence of innervation was evaluated for a single terminal at P9 (29 spines, 32 synaptic contacts) in rat (Sätzler et al, 2002). We tabulated the fraction of type 1 and 2 spines from our large population across age, using accepted criteria for synapse identification in SBEM images (Holcomb et al, 2013;Sanculi et al, 2020;Sätzler et al, 2002;Xiao et al, 2013): (a) parallel orientation of the preand postsynaptic membranes, (b) presence of synaptic vesicles near the presynaptic membrane (<200 nm) in more than one serial section, (c) contact of at least one vesicle with the presynaptic membrane, and added the (d) conservative requirement that these features are present in at least three serial sections (two serial sections shown in Figure 8a,a'). Since en bloc staining for volume EM can reveal postsynaptic densities (PSD), but not reliably, we did not use this feature as one of our criteria.…”
Section: Types 1 and 2 Spines Provide Area For Membrane Apposition mentioning
confidence: 99%
“…Postsynaptic processes that form invaginations in their synaptic partners were discovered using electron microscopy, as this technique affords the requisite resolution to observe structures with dimensions of tens to hundreds of nm in diameter (for review see Petralia et al, 2015;Popov et al, 2011;Sanculi et al, 2020;Spacek & Harris, 2004) with good tracking of cell membranes, staining of intracellular contents, and visualization of all cellular elements. The intertwined nature of spine mats poses additional challenges; the first description of this structure F I G U R E 3 Spine mat comprised of 19 type 2 spines from a P6 principal neuron.…”
Section: Application Of Volume Electron Microscopy To Study Of Somamentioning
confidence: 99%
See 1 more Smart Citation